Facile synthesis of ammonium-decorated cobalt molybdenum fluoride as electroactive material of supercapacitor. (10th December 2022) - Hsiao, Yu-Cheng; Yu, Hsiang-Yu; Lee, Pin-Yan; Yougbaré, Sibidou; Lin, Lu-Yin; Wu, Yung-Fu
Abstract: Bimetallic fluorides are widely applied as the electroactive material of the supercapacitor (SC) due to abundant redox states and high electrical conductivity as clean renewable energy. Ammonia fluoride is regarded as the structure-directing agent for modulating morphology as well as providing F − and NH4 + to respectively form fluoride and hydrogen bonding with promoted electricity transfer routes. In this study, ammonium-decorated cobalt molybdenum fluoride (CoMoFN) is firstly synthesized using the molybdenum salt and the zeolitic imidazolate framework 67 (ZIF67) derived perovskite prepared using NH4 F in the hydrothermal process as the active material of the SC. Molybdenum can enhance electrical conductivity and cyclic stability, as well as confines NH4 + in the framework. Hydrogen bond between NH4 + and F − could promote charge transfer, but the steric hindrance of NH4 + could prohibit ion diffusion. The optimal CoMoFN presents the preferable one-dimensional nanowires-embedded film-like structure, and achieves a specific capacity (CF ) of 33.7 mAh/g at 20 mV/s, while the electrode synthesized without Mo shows a smaller CF value of 17.8 mAh/g. A symmetric SC composed of CoMoFN electrodes shows a maximum energy density of 6.44 Wh/kg at 0.7 kW/kg. Excellent cycling stability with the CF retention of 73% and the Coulombic efficiency higher than 99% after 6500 times charge/discharge processes are also achieved. This work provides significant information about functions of NH4 + on energy storage. It is expected to synthesize more efficient materials based on NH4 + for the energy storage devices. Highlights: Ammonium-decorated cobalt molybdenum fluoride (CoMoFN) is firstly synthesized. Mo and ZIF67-derived perovskite made via NH4 F are precursor for hydrothermal process. Mo maintains NH4 + in framework with hydrogen bonding to promote charge transfer. Supercapacitor with CoMoFN show maximum energy density of 22.9 Wh/kg at 2.5 kW/kg. Capacitance retention of 73 % and Coulombic efficiency of 99 % are got in 6500 cycles.